Energy Harvested IEEE802.15.4 Wireless Body Area Network - Nguyen, Thien; Khan, Jamil; Ngo, Duy (EAI Endorsed Transactions on Energy Web, 2015)
With the increasing demand of wireless body area network (WBAN) for patient monitoring systems, it is necessary to develop efficient energy management systems to either prolong node battery replacement time or to develop batteryless WBAN nodes. In this paper, we introduce an energy harvesting WBAN architecture that combines the energy harvesting system and an adaptable duty cycle adjustment algorithm ABSD (Adaptive Beacon Order, Superframe Order and Duty cycle) to prolong a WBAN node battery lifetime. The paper presents an energy harvesting model to show the effectiveness of human body motion based energy harvester. The paper further analyses the performance of a multi-patient and energy harvested WBAN using our proposed adjustable duty algorithm known as ABSD. The paper also presents several initial simulation results.